Ball mill lining with high wear resistance and preparation process thereof

By using thermal spray granulation and supersonic flame spraying technology of boron nitride, iron chromium powder and tungsten disulfide on the ball mill liner, a porous wear-resistant coating is formed, which solves the problem of shortage of rare metal alloy elements and achieves high wear resistance and high purity.

CN115740462BActive Publication Date: 2025-03-04铜陵有色金属集团股份有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211192061.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-28
Publication Date
2025-03-04
Estimated Expiration
2042-09-28

AI Technical Summary

Technical Problem

Among the existing ball mill lining materials, the shortage of rare metal alloy elements and high cost problems have made it difficult to meet the wear resistance and purity of the lining plate.

Method used

Boron nitride, ferrochrome powder and tungsten disulfide are used to form a porous wear-resistant coating through thermal spray granulation and supersonic flame spraying process, which enhances the wear resistance and corrosion resistance of the lining plate.

Benefits of technology

It significantly improves the wear resistance and purity of the ball mill lining, reduces the use of rare metals, extends the service life of the lining, and reduces the production cost.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a ball mill liner with high wear resistance and a preparation process thereof, comprising the following steps: coating preparation: 60-100 grams of boron nitride, 3 ml-8 ml of a binder and 25-50 grams of ferrochrome powder are stirred in a stirrer, and subjected to ultrasonic treatment, and then 15-25 grams of pre-expanded polystyrene particles with a particle size of 3.0-4.5 microns are added, and then water is added, and the stirring is continued in the stirrer to prepare a mixed slurry; the mixed slurry is formed into boron nitride microspheres by a thermal spray granulation method; the invention reduces the use amount of rare metals by arranging a wear-resistant coating on the surface of the alloy, and the wear-resistant coating forms a unique toughening structure between boron nitride, ferrochrome powder and tungsten disulfide, so that the coating has dual wear resistance, and at the same time, tungsten disulfide reacts chemically with iron to produce a FeS film with a low melting point, which effectively reduces the contact between metal friction, thereby reducing the wear of the metal surface.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lining plates, in particular to a ball mill lining plate with high wear resistance and a preparation process thereof. Background Art

[0002] The ball mill cylinder liner is used to protect the cylinder from direct impact and friction between the grinding body and the material. It also affects the movement of the grinding body. Different forms of liners can be used to adjust the movement of the grinding body to enhance the grinding effect of the grinding body on the material, which helps to improve the grinding efficiency of the ball mill.

[0003] Commonly used lining materials are alloy steels. In order to improve the toughness and wear resistance of alloy steels, alloy elements such as molybdenum, nickel, chromium, tungsten, and vanadium are usually added. With the increasing scarcity of alloy resources, the supply of molybdenum, nickel, chromium, tungsten, vanadium and other alloys is becoming increasingly tight, and the prices are rising rapidly. At the same time, during use, the working surface of the lining is easily worn or corroded, thereby reducing the purity of the material produced. Summary of the invention

[0004] In view of the shortcomings of the prior art, the present invention provides a ball mill liner with high wear resistance and a preparation process thereof. The specific technical scheme is as follows:

[0005] A process for preparing a ball mill liner with high wear resistance comprises the following steps:

[0006] Coating preparation: 60-100 g of boron nitride, 3 ml-8 ml of binder and 25-50 g of ferrochrome powder are stirred in a mixer and ultrasonically treated, then 15-25 g of pre-expanded polystyrene particles with a particle size of 3.0-4.5 μm are added, and then water is added and stirred in the mixer to prepare a mixed slurry;

[0007] The mixed slurry is formed into boron nitride microspheres by a thermal spray granulation method; the microspheres obtained by the thermal spray granulation are separated by a cyclone separation tower to collect microspheres with a particle size of more than 20 microns;

[0008] Sintering the microspheres with a particle size of more than 20 microns at 800° C.-950° C. to form porous boron nitride microspheres;

[0009] The porous boron nitride microspheres prepared in the above steps, 20-40 g of tungsten disulfide powder, and 3 ml-8 ml of a binder are stirred in a blender, and ultrasonically treated, and then water is added and stirred in the blender to prepare a mixed slurry;

[0010] The mixed slurry B is subjected to thermal spray granulation to form composite microspheres; the microspheres obtained by thermal spray granulation are separated by a cyclone separation tower to collect composite microspheres with a particle size of 25-45 microns;

[0011] Alloy smelting: The chemical composition and mass fraction of the alloy are as follows: the weight fraction of its composition is: C is 1-1.3%, Si is 0.5-1.5%, Mn is 11-25%, Cr is 0.8-4%, Mo is 0.3-1.4%, V is 0.3-1%, P≤0.05%, S≤0.05%, and the rest is iron and unavoidable impurities;

[0012] The above combination is mixed, molten steel is melted in a medium frequency electric furnace, cast, quenched, and tempered at 200°C-400°C to obtain an alloy;

[0013] Spraying: The obtained alloy surface to be processed is shot blasted by a shot blasting machine and cleaned. The supersonic flame spraying process is adopted, and the flame speed is ≥2100m / s. The composite microspheres configured above are fed into the flame to generate molten or semi-molten particles, which impact on the alloy working surface at high speed to form a wear-resistant coating.

[0014] According to the improvement of the above technical solution, the temperature of the thermal spray granulation is 150°C-200°C.

[0015] According to the improvement of the above technical solution, the thickness of the cladding layer of the wear-resistant coating in the spraying step is 1.8-2.4 mm.

[0016] According to the improvement of the above technical solution, the binder is any one or a mixture of aluminum dihydrogen phosphate, silica sol, dextrin and sodium carboxymethyl cellulose.

[0017] According to the improvement of the above technical solution, the temperature of the quenching treatment in the alloy smelting step is 1000-1150°C.

[0018] The present invention provides a block liner prepared by the above-mentioned high wear-resistant ball mill liner process, whose length: width: height = 5:3:2.

[0019] Beneficial effects of the present invention:

[0020] A wear-resistant coating is set on the surface of the alloy to reduce the use of rare metals. The wear-resistant coating forms a unique toughening structure between boron nitride, ferrochrome powder and tungsten disulfide, so that the coating has dual wear resistance. At the same time, tungsten disulfide reacts chemically with iron to produce a FeS film with a lower melting point, which effectively reduces the contact between metal friction, thereby reducing the wear of the metal surface. In addition, under conditions where friction generates high temperature, tungsten disulfide will slowly produce oxides. The formation of oxides can inhibit the further oxidation of tungsten disulfide, and the formed oxides also have a lower friction coefficient and lubrication properties similar to tungsten disulfide, thereby reducing the wear between metal surfaces, thereby ensuring the purity of the manufactured material. DETAILED DESCRIPTION

[0021] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0022] Embodiment 1:

[0023] Coating preparation: 60 g of boron nitride, 25 g of ferrochrome powder and 3 ml of binder were stirred in a blender for 30 minutes, and then 15 g of pre-expanded polystyrene particles with a particle size of 3.0 μm were added, and then water was added, and the mixture was stirred in the blender for 20 minutes, and then ultrasonically treated to prepare a mixed slurry;

[0024] The mixed slurry is formed into boron nitride microspheres by a thermal spray granulation method; the temperature of the thermal spray granulation is 150° C. The microspheres obtained by the thermal spray granulation are separated by a cyclone separation tower to collect microspheres with a particle size of more than 20 microns;

[0025] Sintering the microspheres with a particle size of more than 20 micrometers at 800° C. to form porous boron nitride microspheres;

[0026] The porous boron nitride microspheres prepared in the above steps, 25 grams of tungsten disulfide powder and 3 ml of binder were stirred in a blender for 45 minutes, and then water was added, and the mixture was stirred in the blender for 30 minutes, and then ultrasonically treated to prepare a mixed slurry.

[0027] The binder is any one or a mixture of aluminum dihydrogen phosphate, silica sol, dextrin and sodium carboxymethyl cellulose, preferably silica sol, because silica sol can not only be used as a binder, but also can be added as a low-temperature sintering aid to ensure that the porous boron nitride microspheres are kept in a non-collapsed state during the sintering process;

[0028] The mixed slurry B is formed into composite microspheres by a thermal spray granulation method; the temperature of the thermal spray granulation is 200°C-300°C, and the microspheres obtained by the thermal spray granulation are separated by a cyclone separation tower to collect composite microspheres with a particle size of 25-45 microns;

[0029] Alloy smelting: The chemical composition and mass fraction of the alloy are as follows: The weight fractions of the composition are: C is 1%, Si is 0.5%, Mn is 11%, Cr is 0.8%, Mo is 0.3%, V is 0.3%, P is 0.05%, S is 0.05%, and the rest is iron and unavoidable impurities;

[0030] The above combination is mixed, molten steel is melted in a medium frequency electric furnace, and cast into a block liner with a length: width: height = 5:3:2, quenched at a temperature of 1000°C, and then tempered at 200°C to obtain an alloy;

[0031] Spraying: The surface of the alloy to be processed is shot blasted by a shot blasting machine, and then cleaned. The supersonic flame spraying process is adopted, and the flame speed is ≥2100m / s. The composite microspheres configured as above are fed into the flame to produce molten or semi-molten particles, which impact on the working surface of the alloy at high speed to form a wear-resistant coating, wherein the thickness of the coating layer is 1.8-2.4mm, preferably 2mm.

[0032] Boron nitride microspheres are prepared by utilizing the property that slurry spray will evaporate into balls at a high temperature. They are then calcined at a high temperature to remove the pre-expanded polystyrene particles in the microspheres and sintered to form porous boron nitride microspheres with good mechanical strength. Tungsten disulfide is then loaded on the surface of the sintered porous boron nitride microspheres by a spray granulation method to obtain composite microspheres with lubricating properties. The composite microspheres are then coated on the alloy surface with a high-strength, corrosion-resistant and wear-resistant coating using a supersonic flame spraying process.

[0033] During the high-temperature sintering process, the ferrochrome powder will melt into liquid, fill the gaps around the boron nitride microsphere particles, and increase the density of the porous boron nitride microspheres. Due to the frictional heat generation, the use of a boron nitride high thermal conductivity substrate reduces the generation of frictional heat, and can transform high-temperature friction and wear into conditions similar to normal-temperature friction and wear, so that the material's organizational properties are not further affected by the high temperature and undergo other changes, thereby greatly improving the wear resistance of the wear-resistant coating.

[0034] The wear-resistant coating forms a unique toughening structure between boron nitride and tungsten disulfide, which makes the coating have dual wear resistance. At the same time, tungsten disulfide reacts chemically with iron to produce a FeS film with a lower melting point, which effectively reduces the contact between metal friction, thereby reducing the wear of the metal surface. In addition, if the friction generates high temperature, tungsten disulfide will slowly produce oxides. The formation of oxides can inhibit the further oxidation of tungsten disulfide, and the formed oxides also have a lower friction coefficient and lubrication properties similar to tungsten disulfide, thereby reducing the wear between metal surfaces.

[0035] It is coated on the alloy surface by supersonic flame spraying, which has good bonding force and is not easy to fall off. The coating has excellent wear resistance and corrosion resistance.

[0036] Embodiment 2:

[0037] Coating preparation: 80 g of boron nitride, 5 ml of binder and 37 g of ferrochrome powder were stirred in a blender for 38 minutes, and then 20 g of pre-expanded polystyrene particles with a particle size of 3.8 μm were added, and then water was added, and the mixture was stirred in the blender for 27 minutes, and ultrasonically treated to prepare a mixed slurry;

[0038] The mixed slurry is formed into boron nitride microspheres by a thermal spray granulation method; the thermal spray granulation temperature is 170° C. The microspheres obtained by the thermal spray granulation are separated by a cyclone separation tower to collect microspheres with a particle size of more than 20 microns;

[0039] Sintering the microspheres with a particle size of more than 20 microns at 880° C. to form porous boron nitride microspheres;

[0040] The porous boron nitride microspheres prepared in the above steps, 30 g of tungsten disulfide powder and 5 ml of binder were stirred in a blender for 68 minutes, and then water was added, and the mixture was stirred in the blender for 38 minutes, and then ultrasonically treated to prepare a mixed slurry.

[0041] The binder is any one or a mixture of aluminum dihydrogen phosphate, silica sol, dextrin and sodium carboxymethyl cellulose, preferably silica sol, because silica sol can not only be used as a binder, but also can be added as a low-temperature sintering aid to ensure that the porous boron nitride microspheres are kept in a non-collapsed state during the sintering process;

[0042] The mixed slurry B is formed into composite microspheres by a thermal spray granulation method; the thermal spray granulation temperature is 170°C, and the microspheres obtained by the thermal spray granulation are separated by a cyclone separation tower to collect composite microspheres with a particle size of 25-45 microns;

[0043] Alloy smelting: The chemical composition and mass fraction of the alloy are as follows: The weight fractions of the composition are: C is 1.2%, Si is 1%, Mn is 18%, Cr is 2.8%, Mo is 0.6%, V is 0.7%, P is 0.05%, S is 0.05%, and the rest is iron and unavoidable impurities;

[0044] The above combination is mixed, molten steel is melted in a medium frequency electric furnace, and cast into a block liner with a length: width: height = 5:3:2, quenched at a temperature of 1100°C, and then tempered at 300°C to obtain an alloy;

[0045] Spraying: The surface of the alloy to be processed is shot blasted by a shot blasting machine, and then cleaned. The supersonic flame spraying process is adopted, and the flame speed is ≥2100m / s. The composite microspheres configured as above are fed into the flame to produce molten or semi-molten particles, which impact on the working surface of the alloy at high speed to form a wear-resistant coating, wherein the thickness of the coating layer is 1.8-2.4mm, preferably 2mm.

[0046] Embodiment three:

[0047] Coating preparation: 100 g of boron nitride, 8 ml of binder and 50 g of ferrochrome powder were stirred in a blender for 45 minutes, then 25 g of pre-expanded polystyrene particles with a particle size of 4.5 μm were added, and then water was added, and the mixture was stirred in a blender for 35 minutes, and then ultrasonically treated to prepare a mixed slurry;

[0048] The mixed slurry is formed into boron nitride microspheres by a thermal spray granulation method; the temperature of the thermal spray granulation is 300° C. The microspheres obtained by the thermal spray granulation are separated by a cyclone separation tower to collect microspheres with a particle size of more than 20 microns;

[0049] Sintering the microspheres with a particle size of more than 20 micrometers at 950° C. to form porous boron nitride microspheres;

[0050] The porous boron nitride microspheres prepared in the above steps, 40 grams of tungsten disulfide powder and 8 ml of binder were stirred in a blender for 90 minutes, and then water was added, and the mixture was stirred in the blender for 45 minutes, and then ultrasonically treated to prepare a mixed slurry.

[0051] The binder is any one or a mixture of aluminum dihydrogen phosphate, silica sol, dextrin and sodium carboxymethyl cellulose, preferably silica sol, because silica sol can not only be used as a binder, but also can be added as a low-temperature sintering aid to ensure that the porous boron nitride microspheres are kept in a non-collapsed state during the sintering process;

[0052] The mixed slurry B is subjected to a thermal spray granulation method to form composite microspheres; the thermal spray granulation temperature is 300° C. The microspheres obtained by the thermal spray granulation are separated by a cyclone separation tower to collect composite microspheres with a particle size of 25-45 μm;

[0053] Alloy smelting: The chemical composition and mass fraction of the alloy are as follows: The weight fractions of its composition are: C is 1.3%, Si is 1.5%, Mn is 25%, Cr is 4%, Mo is 1.4%, V is 1%, P is 0.05%, S is 0.05%, and the rest is iron and unavoidable impurities;

[0054] The above combination is mixed, molten steel is melted in a medium frequency electric furnace, cast, quenched at a temperature of 1150°C, and tempered at 400°C to obtain an alloy;

[0055] Spraying: The surface of the alloy to be processed is shot blasted by a shot blasting machine, and then cleaned. The supersonic flame spraying process is adopted, and the flame speed is ≥2100m / s. The composite microspheres configured as above are fed into the flame to produce molten or semi-molten particles, which impact on the working surface of the alloy at high speed to form a wear-resistant coating, wherein the thickness of the coating layer is 1.8-2.4mm, preferably 2mm.

[0056] Embodiment 4:

[0057] Alloy smelting: The chemical composition and mass fraction of the alloy are as follows: The weight fractions of the composition are: C is 1.2%, Si is 1%, Mn is 18%, Cr is 2.8%, Mo is 0.6%, V is 0.7%, P is 0.05%, S is 0.05%, and the rest is iron and unavoidable impurities;

[0058] The above combinations are mixed, molten steel is melted in a medium frequency electric furnace, and cast into a block lining plate with a length: width: height = 5:3:2. The lining plate is quenched at a temperature of 1100°C and then tempered at 300°C to obtain an alloy.

[0059] Abrasion resistance test:

[0060] The wear resistance test was carried out using a SFT-2M pin-disc rotary abrasive wear tester. Silicon carbide balls were selected as counter grinding balls. The rotating speed of the turntable was 600 rpm, the load on the sample was 20N, the wear time was 40 minutes, and the wear amount was statistically calculated. The results are shown in the table.

[0061] Example 1 Example 2 Example 3 Example 4 Wear 0.062 0.023 0.048 0.723

[0062] Embodiment 2 is the best solution. The wear-resistant layer can play a greater role in reducing friction, isolates the direct contact between the friction material and the dual material, reduces the amount of wear, and thus improves the wear resistance. The present invention greatly improves the wear resistance of the liner, extends the service life of the liner, improves the operating efficiency, and reduces the production cost. In Embodiment 3, if the tungsten disulfide and boron nitride composite material is excessive, due to friction, the composite material accumulates or even agglomerates on the alloy surface, which reduces the wear resistance.

[0063] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A process for preparing a ball mill liner with high wear resistance, characterized in that: The following steps are involved: Coating preparation: 60-100 g of boron nitride, 3 ml-8 ml of binder and 25-50 g of ferrochrome powder are stirred in a mixer and ultrasonically treated, then 15-25 g of pre-expanded polystyrene particles with a particle size of 3.0-4.5 μm are added, and then water is added and stirred in the mixer to prepare a mixed slurry; The mixed slurry is formed into boron nitride microspheres by a thermal spray granulation method; the microspheres obtained by the thermal spray granulation are separated by a cyclone separation tower to collect microspheres with a particle size of more than 20 microns; Sintering the microspheres with a particle size of more than 20 microns at 800° C.-950° C. to form porous boron nitride microspheres; The porous boron nitride microspheres prepared in the above steps, 20-40 g of tungsten disulfide powder, and 3 ml-8 ml of a binder are stirred in a blender, and ultrasonically treated, and then water is added and stirred in the blender to prepare a mixed slurry; The mixed slurry B is subjected to thermal spray granulation to form composite microspheres; the microspheres obtained by thermal spray granulation are separated by a cyclone separation tower to collect composite microspheres with a particle size of 25-45 microns; Alloy smelting: The chemical composition and mass fraction of the alloy are as follows: the weight fraction of its composition is: C is 1-1.3%, Si is 0.5-1.5%, Mn is 11-25%, Cr is 0.8-4%, Mo is 0.3-1.4%, V is 0.3-1%, P≤0.05%, S≤0.05%, and the rest is iron and unavoidable impurities; The above combination is mixed, molten steel is melted in a medium frequency electric furnace, cast, quenched, and tempered at 200°C-400°C to obtain an alloy; Spraying: The obtained alloy surface to be processed is shot blasted by a shot blasting machine and cleaned. The supersonic flame spraying process is adopted, and the flame speed is ≥2100m / s. The composite microspheres configured above are fed into the flame to generate molten or semi-molten particles, which impact on the alloy working surface at high speed to form a wear-resistant coating; The temperature of the thermal spray granulation is 150°C-200°C; The thickness of the cladding layer of the wear-resistant coating in the spraying step is 1.8-2.4 mm; The binder is any one or a mixture of aluminum dihydrogen phosphate, silica sol, dextrin and sodium carboxymethyl cellulose; The temperature of the quenching treatment in the alloy smelting step is 1000-1150°C.

2. The ball mill liner prepared by the process of claim 1, characterized in that: The lining plate is block-shaped, and its length: width: height = 5:3:2.

Citation Information

Patent Citations

  • Surface coating part for reproduction of ball mill liner plate and manufacturing method for surface coating part

    CN105063499A

  • Compound lubricating anti-wear coating for coating standard piece and preparation method and application of compound lubricating anti-wear coating

    CN105733372A